Teaching Students to Think Critically - Rustamovna, Djurayeva Lola (European Journal of Life Safety and Stability (2660-9630), 2022)
Today's development, students, students are not able to deny their personal critical information to the personal teacher and other things. Our article provides insight and knowledge about what critical thinking is.